Agomelatine: A novel melatonergic antidepressant. Method validation and first exploratory pharmacokinetic study in fasted and fed dogs. (October 2021) - Łebkowska-Wieruszewska, Beata; Ziółkowski, Hubert; Sartini, Irene; Lisowski, Andrzej; Kowalski, Cezary J.; Poapolathep, Amnart; Giorgi, Mario
Abstract: Agomelatine is a novel melatonergic antidepressant, with a non-monoaminergic mechanism of action. The aim of this study was to evaluate its plasma concentrations after a single oral dose of 300 mg/dog in fasted and fed status. The research was carried out in 6 adult healthy Labrador dogs according to a randomized open, single-dose, two-treatment, two-phase, paired 2 × 2 cross-over study. At the end of the study all the animals had received the drug in fasted and fed conditions. The drug concentrations were detected in plasma by a validated LC-MS/MS analytical method. The plasma concentrations of agomelatine were found to be extremely variable in both groups as well as the pharmacokinetic profiles. Due to these variable findings the only reliable pharmacokinetic parameters were assessed as Cmax (31.8 vs 15.7 ng/mL), Tmax (0.75 vs 4 h) and AUC (155 vs 52 ng h/mL) in fasted and fed status, respectively. Unfortunately, as a pioneer study, the small animal sample size used along with the unanticipated variability did not allow to neither statistically estimate if food can affect the pharmacokinetics of agomelatine nor recommend agomelatine for off-label therapies in canine species. Further studies are warranted to clarify this issue. Highlights: Plasma concentrations of agomelatine were found to be extremely variable. In fed group the absorption was delayed. The findings of the present study suggest agomelatine not recommendable for administrations in dogs.